MENINGKATKAN PEMAHAMAN BELAJAR SISWA MENGGUNAKAN MEDIA PRESENTASI BERBASIS QUIZIZZ PADA PEMBELAJARAN IPAS KELAS IV SD - Muhammad Sidik; Destrinelli; Muhammmad Sholeh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low level of students' learning comprehension in grade IV of SDN 55/I Sridadi in science learning. This is supported by the results of observations that have been made. The cause of the low level of students' learning comprehension in science learning is due to the learning media that is not interesting. This study aims to describe the use of presentation media based on Quizizz in improving students' learning comprehension in science material in grade IV of SDN 55/I Sridadi. This research was conducted at SDN 55/I Sridadi. The subjects of the study were 23 students in grade IV of SDN 55/I Sridadi, 12 males and 11 females. This study used a classroom action research methodology that was carried out in two cycles, each cycle consisting of two meetings with the following stages: planning, implementation, observation and reflection. The research data were analyzed qualitatively and quantitatively. The results showed that the application of presentation media based on Quizizz was able to improve students' learning comprehension levels according to the established criteria. In cycle I, the percentage of successful actions in the first meeting was 45.10%, which increased to 57.33% in the second meeting. While in cycle II, the percentage of success in the first meeting reached 72.28%, and increased to 83.42% in the second meeting.